2021
DOI: 10.3389/fphar.2021.642881
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Residues in the Carboxy Terminus of the Dopamine Transporter Involved in the G Protein βγ-Induced Dopamine Efflux

Abstract: The dopamine transporter (DAT) plays a crucial role in the regulation of brain dopamine (DA) homeostasis through the re-uptake of DA back into the presynaptic terminal. In addition to re-uptake, DAT is also able to release DA through a process referred to as DAT-mediated DA efflux. This is the mechanism by which potent and highly addictive psychostimulants, such as amphetamine (AMPH) and its analogues, increase extracellular DA levels in motivational and reward areas of the brain. Recently, we discovered that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Alternatively, antagonism of KOR could further disrupt the potentially enhanced interaction of DAT Val559 with proteins and lipids that bias DAT towards more efflux-prone states (49,(93)(94)(95)(96). Activated Gbg proteins have also been found to induce DA efflux similar to that seen with DAT Val559 and amphetamines (44,45). Whether the pathways involved with KOR antagonism intersect with this mechanism and its regulators are worthy of study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, antagonism of KOR could further disrupt the potentially enhanced interaction of DAT Val559 with proteins and lipids that bias DAT towards more efflux-prone states (49,(93)(94)(95)(96). Activated Gbg proteins have also been found to induce DA efflux similar to that seen with DAT Val559 and amphetamines (44,45). Whether the pathways involved with KOR antagonism intersect with this mechanism and its regulators are worthy of study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ADE has now been recognized as a functional correlate of multiple disease-associated DAT variants (21,30,34,41,42) and can also be triggered in wildtype (WT) DAT via G protein interactions (44,45), extending the ADE phenotype beyond that seen with rare genetic variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to exogenous agents like amphetamines, certain intracellular signaling mechanisms, such as protein kinase C (PKC) and Ca+2/calmodulin-dependent protein kinase II (CAMKII), can also trigger transporter-mediated efflux [11,12]. Recent studies conducted by our group have demonstrated that G protein βγ subunits can bind to DAT and facilitate DA efflux [13,14]. This effect has been observed in transfected cells, brain slices, and in vivo [13,15].…”
Section: Introductionmentioning
confidence: 95%
“…This phosphorylation can be mediated by CaMKIIα and facilitated by an interaction of the kinase with the DAT C-terminus ( 25 ). AMPH-induced efflux might also be regulated by the interaction of DAT with syntaxin1A ( 30 ), G protein βγ subunits and the neuronal GTPase, Rit2 ( 31 , 32 , 33 ), as well as by lipid messengers ( e.g ., phosphatidylinositol 4,5-bisphosphate) ( 34 ). Taken together, multiple mechanisms have been implicated in AMPH-induced efflux; however, since many studies have been done in heterologous cells, the picture is still blurry as to what mechanisms represent the key drivers of efflux in dopaminergic (DArgic) neurons ( 35 ).…”
mentioning
confidence: 99%